2011
DOI: 10.2139/ssrn.2114337
|View full text |Cite
|
Sign up to set email alerts
|

International Evidence on Food Consumption Patterns: An Update Using 2005 International Comparison Program Data

Abstract: The U.S. Department of Agriculture (USDA) prohibits discrimination in all its programs and activities on the basis of race, color, national origin, age, disability, and, where applicable, sex, marital status, familial status, parental status, religion, sexual orientation, genetic information, political beliefs, reprisal, or because all or a part of an individual's income is derived from any public assistance program. (Not all prohibited bases apply to all programs.) Persons with disabilities who require altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(168 citation statements)
references
References 1 publication
6
158
1
3
Order By: Relevance
“…Cross-country demand studies have found that income elasticities of demand for food items generally decline as per capita income increases (Muhammad et al, 2011;Yu et al, 2003). Among various food product categories, Muhammad et al (2011) found that income elasticities for cereals decline the most as per capita income increases, while declines for meat products are smaller.…”
Section: Per Capita Incomementioning
confidence: 99%
“…Cross-country demand studies have found that income elasticities of demand for food items generally decline as per capita income increases (Muhammad et al, 2011;Yu et al, 2003). Among various food product categories, Muhammad et al (2011) found that income elasticities for cereals decline the most as per capita income increases, while declines for meat products are smaller.…”
Section: Per Capita Incomementioning
confidence: 99%
“…The yield effects seem much higher in developing countries [34,52], while lower food prices benefit the poor, for whom food costs constitute a relatively larger share of the daily budget [60]. Mahaffey et al [5], estimating the cost of a global ban on GMOs, surprisingly find that the largest winners of such ban would end up being two major GMO growers: the USA and Brazil.…”
Section: Distributional Effects and Political Economy Factorsmentioning
confidence: 99%
“…However, the fact that the flexibilities of the relative price in relation to the "non-food" supply volume are also negative (for wealthier countries) may be considered as rather unexpected 10 The flexibilities achieved in the Theil-type models for ICP 2005and ICP 1996(Meade, Regmi, Seale and Muhammed, 2014Muhammad, Seale, Meade and Regmi, 2013;Regmi and Seale, 2010;Seale Regmi and Bernstein, 2003) cannot be directly compared with the flexibilities for ICP 2011 presented in Figure 3. Firstly, the flexibilities presented in Figure 3 are calculated in line with the classical Marshall's definition, whereas the flexibilities from the above-mentioned works are defined in different manner.…”
Section: (353) 2017mentioning
confidence: 99%